How green intellectual capital and green commitment shape environmental performance: The mediating role of pro-environmental behavior - Zainal Abidin Marasabessy; Ummi Salamah Tianotak; Noviyanti Soleman (Universitas Ahmad Dahlan, 2026)
Purpose-The demand for sustainable practices is driving businesses to improve their environmental performance. This performance is influenced by an organization’s environmental resources and commitment. This study examines the positive effects of green intellectual capital and green commitment on environmental performance, with pro-environmental behavior serving as an intervening variable. Methodology-This study employs a quantitative approach involving owners and operators of batik-related micro, small, and medium enterprises in Yogyakarta, Indonesia. A total of 160 samples were selected using purposive sampling. Data were collected through the distribution of questionnaires administered both online and offline. The primary data were analyzed using SmartPLS, including tests of validity and reliability, as well as hypothesis testing. Findings-This study is limited to 160 batik micro, small, and medium enterprises in Yogyakarta; therefore, any generalization of the findings to other business sectors and regions should be made with caution. Additionally, using data based on respondents’ perceptions may introduce subjective bias. Future research is recommended to expand the sample size, employ a longitudinal design, and consider other variables that may influence environmental performance. Novelty-This study examines environmental performance by integrating the natural resource-based view and the ability–motivation–opportunity theories. It highlights the roles of green intellectual capital and green commitment in the context of micro, small, and medium enterprises, a topic that remains relatively under-explored in the literature. Furthermore, this study confirms the relationship pathway between green commitment as a predictor, pro-environmental behavior as a mediator, and environmental performance as an outcome. This relationship has been rarely explored in previous research.